2021
DOI: 10.5538/2385-703x.2021.17.14
|View full text |Cite
|
Sign up to set email alerts
|

Primeros resultados de una intervención enfermera sobre el abordaje del tabaquismo en personas con un trastorno mental grave

Abstract: Introducción: se ha encontrado una importante relación entre el consumo de tabaco y distintos trastornos relacionados con la salud mental, observándose una mayor prevalencia de consumo, mayor dependencia a la nicotina, menores intentos de abandono y mayor dificultad para conseguir la abstinencia.Objetivo: evaluar la efectividad de una intervención enfermera sobre el abordaje del tabaquismo para generar motivación en la reducción del consumo de tabaco o una cesación tabáquica completa a personas con un trastorn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…13,34,40 This acceptance on behalf of the health professionals is especially important in the case of nurses, since they are an essential component of the nurse-patient therapeutic relationship. 39,41 At this stage of the recovery process, besides the family and professionals, the importance of support and understanding from peers was also highlighted. 42 Several studies have shown this type of support to be a cornerstone of the recovery process.…”
Section: Discussionmentioning
confidence: 99%
“…13,34,40 This acceptance on behalf of the health professionals is especially important in the case of nurses, since they are an essential component of the nurse-patient therapeutic relationship. 39,41 At this stage of the recovery process, besides the family and professionals, the importance of support and understanding from peers was also highlighted. 42 Several studies have shown this type of support to be a cornerstone of the recovery process.…”
Section: Discussionmentioning
confidence: 99%